2007
DOI: 10.1525/aeq.2007.38.4.380
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Contradictory Communities of Practice in Learning to Teach for Social Justice

Abstract: In this article, I explore the contradictions that four new teachers experienced as their commitments to social justice collide with urban school culture. Framed within Jean Lave and Etienne Wenger's (1999) theory of situated learning and development concepts of identity, practice, and relationships illustrate how teachers' ideals are challenged as socializing features of two communities of practice-the universities and schools-intersect in new teachers' development. This research contributes empirical evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 11 publications
0
30
0
2
Order By: Relevance
“…The call of collaborative communities of practice that support teachers' situated learning in creating transformative practices (Flores, ) is supported by students' participation in the See Blue STEM Camp. Students who participate in STEM camp are able to learn more about the STEM fields by communicating with their peers about the days' activities than they would in a traditional classroom setting.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…The call of collaborative communities of practice that support teachers' situated learning in creating transformative practices (Flores, ) is supported by students' participation in the See Blue STEM Camp. Students who participate in STEM camp are able to learn more about the STEM fields by communicating with their peers about the days' activities than they would in a traditional classroom setting.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…(p. 564) In the time since the data were collected, both teachers report more pressure to teach standardized curriculum. Flores (2007) explains that teachers who teach in Title I schools, have more pressure to teach an institutionalized curriculum rather than develop curriculum that responds to the diverse students in their classes.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicts between teachers' ideals and the challenges of living them in practice may create a productive tension that could lead to collaboration with colleagues or experimentation with new methods or materials. However, researchers have shown that such conflicts may also lead to frustration and feelings of failure (Agarwal et al., ; Flores, ).…”
Section: Preserving Personal Integrity and The Integrity Of Teachingmentioning
confidence: 99%